Platelet number and function alterations in preclinical models of sterile inflammation and sepsis patients: implications in the pathophysiology and treatment of inflammation. (April 2022) - Villa-Fajardo, María; Palma, María Cecilia Yáñez; Acebes-Huerta, Andrea; Martínez-Botía, Patricia; Meinders, Marjolein; Nolte, Martijn A.; Cuesta, Celina Benavente; Eble, Johannes A.; del Castillo, Juan González; Martín-Sánchez, Francisco Javier; Gutiérrez, Laura
Abstract: Platelets are the blood cells in charge of maintaining the body hemostasis, recognising the damaged vessel wall, and providing the appropriate cellular surface for the coagulation cascade to act locally. Additionally, platelets are active immunomodulators. At the crossroads of hemostasis and inflammation, platelets may exert either beneficial actions or participate in pathological manifestations, and have been associated with the prothrombotic nature of multi-organ failure in systemic inflammation. Platelet number alterations have been reported in septis, and platelet transfusions are given to thrombocytopenic patients. However, the risk to develop transfusion related acute lung injury (TRALI) is higher in sepsis patients. In this manuscript we show that platelets produced during inflammation in preclinical mouse models of sterile inflammation display lower aggregation capacity when stimulating certain receptors, while responses through other receptors remain intact, and we name them "inflammation-conditioned" platelets. In a cohort of sepsis patients, we observed, as previously reported, alterations in the number of platelets and platelet hyperreactivity. Furthermore, we identified a receptor-wise platelet aggregation response disbalance in these patients, although not similar to platelets from preclinical models of sterile inflammation. Interestingly, we generated evidence supporting the notion that platelet aggregation capacity disbalance was partially triggered by plasma components from sepsis patients. Our findings have implications in the indication of platelet transfusions in sepsis patients: Are fully functional platelets suitable for transfusion in sepsis patients? Current Clinical Trials (RESCUE) will answer whether platelet production stimulation with thrombopoietin receptor agonists (TPO-RAs) could be a substitute of platelet transfusions.